THE PRINCIPLE PRO HOMINE AS INSTRUMENT OF INTEGRAL PROTECTION THE HUMAN BEING IN THE WORK RELATIONSHIP - Bittencourt, Luiz Antônio da Silva (2020)
This article aims to present a response to the three questions about the protection of man in labor relations: what is it to be protected? Whom to be protected? And how to be protected? In an attempt to provide answers to these three questions, starting from the current Brazilian legislative context, it will seek to comply with international legislation, treaties and conventions ratified by Brazil. In the process of this reflection, the principle pro homine, which is inscribed in several international diplomas, notably in art. 29b of the American Convention on Human Rights (ACHR), art. 4th the Protocol of San Salvador, among others, will be both the guiding thread and the way that will be found to give satisfactory answer to all the structural structural reforms that are being faced in our legislation. The principle of pro homine, well understood and implemented, will enable the full protection of the human being, for guiding the lawyers and legislators in applying standards that are more protective range in the working relationship, taking the man not as a mere employee but as one which, in the working relationship, develops as a human being, person.